Characterization of PEGylated Asparaginase: New Opportunities from NMR Analysis of Large PEGylated Therapeutics. Issue 8 (9th January 2019) - Cerofolini, Linda; Giuntini, Stefano; Carlon, Azzurra; Ravera, Enrico; Calderone, Vito; Fragai, Marco; Parigi, Giacomo; Luchinat, Claudio
Abstract: Resonance assignment and structural characterization of pharmacologically relevant proteins promise to improve understanding and safety of these proteins by rational design. However, the PEG coating that is used to evade the immune system also causes these molecules to "evade" the standard structural biology methodologies. We here demonstrate that it is possible to obtain the resonance assignment and a reliable structural model of large PEGylated proteins through an integrated approach encompassing NMR and X‐ray crystallography. Abstract : Coating a protein with PEG may have structural consequences, but no single biophysical methodology can spot the possible modifications. This limitation has been overcome by the integration of solution and solid‐state NMR data, relaxometry, and X‐ray crystallography for the characterization of a PEGylated enzyme used in clinical practice.